Pengaruh Literasi Halal, Labelisasi Halal, dan Gaya Hidup Terhadap Keputusan Pembelian Minuman Halal Dalam Kemasan Pada Masyarakat Muslim di Kota Surabaya - Eva Natasha; Ach. Yasin (ITB AAS INDONESIA Surakarta, 2026)
The growing consumption of packaged beverages among Muslims, along with the growth of the halal industry, has made halal literacy, halal labeling, and lifestyle key factors influencing purchasing decisions. However, there are still differences in consumer understanding of product halalness, attention to halal labels, and diverse lifestyles that influence purchasing behavior. This study aims to analyze the influence of halal literacy, halal labeling, and lifestyle on halal drinks packaged beverage purchasing decisions among the Muslim community in Surabaya. This research is a quantitative study with an associative research design. The study was conducted in Surabaya, with Muslim consumers of packaged beverages as subjects. The data source used was primary data obtained through questionnaires. Data analysis was performed using multiple linear regression with SPSS through instrument testing, classical assumption testing, t-tests, F-tests, and coefficient of determination tests. The results showed that halal literacy, halal labeling, and lifestyle partially and simultaneously had a positive and significant influence on purchasing decisions for packaged beverages among Muslims in Surabaya. This study concluded that halal literacy, halal labeling, and lifestyle are important factors in increasing purchasing decisions for packaged beverages. Therefore, the government, BPJPH (Indonesian Food and Drug Authority), and business actors are advised to improve halal literacy education, strengthen the implementation of halal labeling, and develop marketing strategies that align with the lifestyles of Muslim consumers.